2019
DOI: 10.1038/s41380-019-0474-5
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral cytokine levels and response to antidepressant treatment in depression: a systematic review and meta-analysis

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
148
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 269 publications
(186 citation statements)
references
References 69 publications
6
148
1
3
Order By: Relevance
“…Meta-analyses of longitudinal studies have shown that antidepressant treatment (on average, for 6-12 weeks) is associated with decreases in serum or plasma cytokines, such as IL-6 and TNF-alpha, both in general 40 and for SSRIs in particular 41 , with the most recent meta-analyses showing that TNF-alpha, but not IL-6, is differentially affected in responders only 42 . Data on longitudinal changes in mRNA expression are much more limited; for example, we published 15 that 8-weeks of antidepressants (escitalopram or nortriptyline) decrease IL-6 mRNA, but this is driven by responders only, while TNF-alpha mRNA levels do not change.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses of longitudinal studies have shown that antidepressant treatment (on average, for 6-12 weeks) is associated with decreases in serum or plasma cytokines, such as IL-6 and TNF-alpha, both in general 40 and for SSRIs in particular 41 , with the most recent meta-analyses showing that TNF-alpha, but not IL-6, is differentially affected in responders only 42 . Data on longitudinal changes in mRNA expression are much more limited; for example, we published 15 that 8-weeks of antidepressants (escitalopram or nortriptyline) decrease IL-6 mRNA, but this is driven by responders only, while TNF-alpha mRNA levels do not change.…”
Section: Discussionmentioning
confidence: 99%
“…30 Other meta-analyses have shown that traditional antidepressants (for example selective serotonin reuptake inhibitors (SSRIs) and serotonin-noradrenaline reuptake inhibitors) are associated with a reduction in IL-6, TNF-α and CCL-2 31 and that persistently elevated TNF-α is associated with treatment resistance. 32,33 Retrospective cohort studies indicate that inflammation may play a role in the onset of mood symptoms and that elevated peripheral inflammatory markers in early life are predictive of adult depressive symptomology. 34,35 Within the literature, there is significant heterogeneity between studies and in particular, there are substantial differences in how comorbidities are controlled for.…”
Section: Resultsmentioning
confidence: 99%
“…Further clinical research is essential to clearly identify biomarkers for the assessment of inflammation-vascular-autonomic dysfunction, which could be used for personalized prevention and treatment of CVD in depressive patients. Currently, increasing attention is focused on the efficacy of anti-inflammatory treatment in major depressive disorder [84,85]; thus, the development of novel therapeutic interventions targeting the immune, vascular, and autonomic nervous systems in MDD is of particular importance.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%